Patch-based techniques in medical imaging : 4th International Workshop, Patch-MI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings /: 4th International Workshop, Patch-MI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 20, 2018, Proceedings. (2018) - Unknown
No abstract available